The impact of government environmental attention on public health: Implications for corporate sustainable development - Jinfang Tian; Jinfang Tian; Shu Zhang; Xudong Wei; Shan Zhuang; Mingxuan Zhang (Frontiers in Environmental Science, 2022)
As major contributors to air pollution, enterprises have a growing impact on the environment, which puts public health at risk and requires urgent government intervention. This study constructs a government environmental attention variable via textual analysis of Chinese government work reports from 2004 to 2017, and examines the impact of government environmental attention on public health. We find that local government environmental attention has a significant and positive impact on public health. Our mechanism analysis suggests that government environmental governance investment acts as an important mediating channel in transferring the impact of government environmental attention on public health. Moreover, we find that the impact of government environmental attention on public health is more pronounced in Central and Western China, in low-openness regions, and after the incorporation of environmental performance in the cadre evaluation system in 2006. Overall, our study links micro-level environmental issues with macro-level governmental behaviors, providing a new perspective for future research on the influencing factors of public health and practical implications for corporate sustainable development.